2019
DOI: 10.4155/tde-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Glibenclamide and quercetin-loaded Chitosan Nanogels Targeting Skin Permeation

Abstract: Aim: Our aim was to develop and characterize a nanogel formulation containing both glibenclamide and quercetin and to explore the permeation profile of this combination. Methods: Drug-loaded nanogel was prepared by ionic gelation. In addition, optimum encapsulation efficiencies of glibenclamide and quercetin were also obtained. The average nanoparticle size at optimum conditions was determined by Zetasizer. Results: The particle size of the nanogel was found to be 370.4 ± 4.78 nm with a polydispersity index of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…16,46 The opposite action of native quercetin and Au Qur NP towards the cell can be explained by absorption kinetics and bioavailability of trapped quercetin material. 47 Our data is consistent with earlier report of accelerated wound healing by quercetin loaded chitosan NPs through TGFb1-dependent mechanism, 48 and we believe it can be used as topical agent for dermal wound healing. Fig.…”
Section: Resultssupporting
confidence: 91%
“…16,46 The opposite action of native quercetin and Au Qur NP towards the cell can be explained by absorption kinetics and bioavailability of trapped quercetin material. 47 Our data is consistent with earlier report of accelerated wound healing by quercetin loaded chitosan NPs through TGFb1-dependent mechanism, 48 and we believe it can be used as topical agent for dermal wound healing. Fig.…”
Section: Resultssupporting
confidence: 91%
“…CS-embelin NPs were effective against LPO in this study. 38,39 Previous studies have reported that oxidants and LPO are negatively correlated with antioxidants. Reduced levels of cellular antioxidants and accelerated free radical production can be critical factors in arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…89 Recently, glibenclamide-loaded chitosan nanogels have been reported as suitable topical formulations to treat diabetes with the advantage of enhanced skin permeation. 90 Hydrogels are the most studied polymeric nanocarriers as drug delivery systems, they have the advantages of higher stability in comparison with nanoemulsions and suspensions. Gelembedded vesicles are topical formulations with the advantage of skin permeation enhancement, improved dermal bioavailability, and better patient compliance.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%